AuthorSynth: a collaboration network and behaviorally-based visualization tool of activation reports from the neuroscience literature - Sochat, Vanessa V. (Frontiers in Neuroinformatics, 2015)
Targeted collaboration is becoming more challenging with the ever-increasing number of publications, conferences, and academic responsibilities that the modern-day researcher must synthesize. Specifically, the field of neuroimaging had roughly 10,000 new papers in PubMed for the year 2013, presenting tens of thousands of international authors, each a potential collaborator working on some sub-domain in the field. To remove the burden of synthesizing an entire corpus of publications, talks, and conference interactions to find and assess collaborations, we combine meta-analytical neuroimaging informatics methods with machine learning and network analysis toward this goal. We present “AuthorSynth,” (http://www.vbmis.com/bmi/authorSynth) a novel application prototype that includes 1) a collaboration network to identify researchers with similar results reported in the literature, and 2) a 2D plot - “brain lattice” - to visually summarize a single author’s contribution to the field, and allow for searching of authors based on behavioral terms. This method capitalizes on intelligent synthesis of the neuroimaging literature, and demonstrates that data-driven approaches can be used to confirm existing collaborations, reveal potential ones, and identify gaps in published knowledge. We believe this tool exemplifies how methods from neuroimaging informatics can better inform researchers about progress and knowledge in the field, and enhance the modern workflow of finding collaborations.